Research on Marketing Development under the Background of Artificial Intelligence Technology. Issue 1 (January 2021) - Lu, Wenyang
Abstract: In today's society, my country's science and technology has made many advances and breakthroughs on the original basis. Among them, artificial intelligence technology has been further improved in this new market environment, and the operating methods of all sectors of society have undergone earth-shaking changes under the guidance of this new technology. Many traditional industries on this basis have a more brilliant development prospects. As an important part of various enterprises, marketing work has also undergone new changes due to the application of artificial intelligence technology. Especially in an environment where various information and data can be shared and used via the Internet, artificial intelligence technology can show all its advantages. All data information can be refined analysis through advanced computer system.